Remarks by Michael Scharf. (2022) - Scharf, Michael
Abstract : Thank you so much, Catherine. As Catherine said, I am Michael Scharf, dean of Case Western Reserve University School of Law. We are very pleased to be sponsoring this program today, a conversation with Judge Chile Eboe-Osuji, one of my oldest friends in this field and recipient of the Butcher Medal.